OC-036 International Assessment of Outcome of Upper GI Haemorrhage at Weekends. (17th August 2016) - Murray, IA; Dalton, HR; Stanley, A; Ngu, JH; Maybin, B; Eid, M; Madsen, KG; Abazi, R; Ashraf, H; Abdelrahim, M; Lissmann, R; Herrod, J; et al.
Abstract : Introduction: Weekend admissions have been associated with higher mortality. For upper gastrointestinal haemorrhage (UGIH) some studies show significantly increased mortality and less early endoscopy while the UK UGIH audit reported no difference. We studied whether out of hours (OOH) admissions were sicker and/or had higher mortality. Methods: Prospective study over 12 months (from March 2014) from 2 UK and 2 international centres. Admission time, demographics, pulse, BP, lab results, endoscopy findings, further procedures and 30 d mortality were recorded. 3 pre-endoscopy scores (Glasgow Blatchford (GBS), AIMS65 and admission Rockall scores) and 2 post-endoscopy scores (PNED and full Rockall scores) were determined. Chi-squared, Fisher's exact and Kruskal-Wallis tests were used as appropriate. A two-tailed significance level of 5% was used. Results: 2118 pconsecutive atients, 60% male, median age 66 years were seen. There were no significant differences in mortality, need for endoscopic therapy, surgery/embolisation or rebleeding in both UK and non-UK centres. There were no differences in comorbidity, mean ASA 2.3, pulse or BP although weekday admissions had a lower Hb (110 g/l vs 118 g/l (weeknight) vs 117 g/l (weekend) p < 0.001 and higher GBS (p < 0.05). No difference in peptic ulcer disease or varices incidence between periods although more weekday admissions had normal endoscopy (p = 0.002). OOH admissions were less likely to have an endoscopy (30% not endoscoped vs 23% for weekday admission p < 0.005). Time to endoscopy was less for weeknight admissions (13 h vs 17 h for weekend and 20 h for weekday admissions p = 0.0001). 67% weekday, 75% weeknight and 60% weekend admissions had their endoscopy within 24 hours. 2118 consecutive patients admitted March 2014-March 2015 from Glasgow (600), Truro (544), Odense (541) and Singapore (433). Data shown are mean [95% CI] or number (%). Conclusion: There is no difference in mortality in patients admitted with UGIH OOH compared to weekday admissions. The severity of UGIH was not related to time of admission. Similar findings were noted in the 2 UK centres and internationally. Disclosure of Interest: None Declared